1984
DOI: 10.1002/bjs.1800710507
|View full text |Cite
|
Sign up to set email alerts
|

Vascular injury with associated bone and joint trauma

Abstract: The clinical presentation and management of 102 vascular injuries associated with bone and joint trauma, in 100 patients over a 6-year period, is reviewed. Eighty-three injuries involved the lower limbs. Amputation became necessary in 16 patients. In 12 this was directly attributable to delay in revascularization or the extent of the soft tissue injury with consequent sepsis. Early graft occlusion in an otherwise salvageable limb occurred in four patients (3.9 per cent). Successful therapy involves close co-op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…In clinic, the pulse of dorsal pedal artery can still be felt in some TPF patients with PAI in the early stage. Meek [17] et al found that the weaker pulse than normal can be felt at the distal end in about 22% of patients with injury of major limb arteries, also consistent with the ndings in this study that the weaker pulse of dorsal pedal artery than that at the contralateral side could be felt in 5 cases in the early stage. The possible reason is that the popliteal artery has not been completely ruptured but severely contused in some patients with PAI, causing damage to the artery intima and thrombosis, so some blood supply remains in the initial stage.…”
Section: Discussionsupporting
confidence: 92%
“…In clinic, the pulse of dorsal pedal artery can still be felt in some TPF patients with PAI in the early stage. Meek [17] et al found that the weaker pulse than normal can be felt at the distal end in about 22% of patients with injury of major limb arteries, also consistent with the ndings in this study that the weaker pulse of dorsal pedal artery than that at the contralateral side could be felt in 5 cases in the early stage. The possible reason is that the popliteal artery has not been completely ruptured but severely contused in some patients with PAI, causing damage to the artery intima and thrombosis, so some blood supply remains in the initial stage.…”
Section: Discussionsupporting
confidence: 92%
“…In clinic, the pulse of dorsal pedal artery can still be felt in some TPF patients with PAI in the early stage. Meek [13] et al found that the weaker pulse than normal can be felt at the distal end in about 22% of patients with injury of major limb arteries, also consistent with the ndings in this study that the weaker pulse of dorsal pedal artery than that at the contralateral side could be felt in 5 cases in the early stage. The possible reason is that the popliteal artery has not been completely ruptured but severely contused in some patients with PAI, causing damage to the artery intima and thrombosis, so some blood supply remains in the initial stage.…”
Section: Discussionsupporting
confidence: 92%
“…Compound fractures are usually associated with extensive soft tissue damage and significant interruption of collateral circulation, which increases the risk of critical ischemia, infection, and limb loss. 26 In this series, explosive injuries carried the highest risk of amputation. These injuries are usually associated with significant soft tissue damage and are more likely to affect the arterial supply at more than one level.…”
Section: Discussionmentioning
confidence: 92%
“…Compound fractures are usually associated with extensive soft tissue damage and significant interruption of collateral circulation, which increases the risk of critical ischemia, infection, and limb loss. 26…”
Section: Discussionmentioning
confidence: 99%